PENGARUH PENGENDALIAN MANAJEMEN TERHADAP KINERJA KARYAWAN PADA PT GOLDEN LEAVES JAYA ABADI (Magister Manajemen Universitas Wisnuwardhana, 2022)
Management control is a company activity that is the last bastion to ensure that all components of the company work according to predetermined standards. This assurance needs to be obtained as part of the efforts of the Management and the company to provide the best results to consumers. Success in the control process, in several studies will have an impact on various aspects of company activities such as achieving efficiency and effectiveness in the production process. By using a quantitative approach, involving employees of the production department as respondents, this study attempts to find a correlation between management control and employee performance.